1995
DOI: 10.1590/s0104-79301995000200004
|View full text |Cite
|
Sign up to set email alerts
|

Human Envenomations Due to Snakebites in Marilia, State of São Paulo, Brazil. A Retrospective Epidemiological Study

Abstract: Eighty-four patients bitten by venomous snakes were studied retrospectively at the School of Medicine of Marilia from January 1990 to August 1994. The majority of these patients were rural workers, 65 (77.38%) males and 19 (22.62%) females, aged eight to seventy-five. Forty-three (51.19%) patients were diagnosed as having been bitten by snakes of the genus Bothrops and 41 (48.81%) by Crotalus. Fifty-eight patients (69.04%) were bitten in the legs and 26 (30.96%) in the arms. January, March, April and November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
2
4
0
3
Order By: Relevance
“…Considering the accident place and the victim's gender and age, the obtained data were similar to those reported in literature (5,9,13,15,26).…”
Section: Resultssupporting
confidence: 87%
“…Considering the accident place and the victim's gender and age, the obtained data were similar to those reported in literature (5,9,13,15,26).…”
Section: Resultssupporting
confidence: 87%
“…For the same reason, males were more afflicted with bites than females. Similar results have been reported by many studies in Africa and Asia (18,21,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 91%
“…This work also demonstrated that young adults and adolescents are more affected by snakebites, mainly due to their greater exposure through outdoor activities, particularly agricultural ones (22,(24)(25)(26). For the same reason, males were more afflicted with bites than females.…”
Section: Discussionmentioning
confidence: 58%
“…O envenenamento causado por serpentes constitui um dos problemas mais importantes na Medicina e Medicina Veterinária nos países tropicais, devido a sua alta incidência, gravidade e seqüelas das lesões (Sgarbi et al 1995, Berrocal et al 1998, Pinho et al 2000, Sangiorgio et al 2008. Na América do Sul os gêneros Bothrops e Crotalus são responsáveis pela maioria dos acidentes ofídicos envolvendo seres humanos e animais (Dourado et al 1988, Kouyoumdjian 1990, Sorensen 1990, Barraviera 1991, Ribeiro 1991, Méndez & Riet-Correa 1995, Sgarbi et al 1995, Pinho et al 2000.…”
Section: Introductionunclassified
“…Na América do Sul os gêneros Bothrops e Crotalus são responsáveis pela maioria dos acidentes ofídicos envolvendo seres humanos e animais (Dourado et al 1988, Kouyoumdjian 1990, Sorensen 1990, Barraviera 1991, Ribeiro 1991, Méndez & Riet-Correa 1995, Sgarbi et al 1995, Pinho et al 2000. O gênero Crotalus da família Crotalidae e sua subespécie Crotalus durissus terrificus são a segunda mais importante causa de acidentes no Brasil (Nogueira et al 2007).…”
Section: Introductionunclassified